The decade-long cryptocurrencies and the blockchain rollercoaster: Mapping the intellectual structure and charting future directions - Klarin, Anton (2020)
Recent advances in science mapping allowed to analyze the entire intellectual structure of blockchain and cryptocurrencies in business-related disciplines to identify 174 academic articles as well as 1482 practitioner-oriented articles published since the inception of cryptocurrencies in 2008 to highlight key trends of the published outputs. The results demonstrate academic research done by 389 authors in 296 organizations based in 50 countries that only just initiated the conversation on four major streams of the literature—Bitcoin and cryptocurrencies; blockchain adoption; cryptocurrency and blockchain environment; and business model innovations. When comparing academic scholarship to practitioner-oriented literature, the results demonstrate that practitioners discussed investor-related themes, cryptocurrency intrinsic value, political-economic sphere, and the impact of cryptocurrency and blockchain technologies on the wider society in greater detail. As a result, a number of themes are identified and discussed that could align academic and practitioner interests and provide guidance for further research in this important field.